Rapid identification of Staphylococcus aureus, Vibrio parahaemolyticus and Shigella sonnei in foods by solid phase microextraction coupled with gas chromatography–mass spectrometry. (1st October 2018) - Wang, Yu; Liu, Sijing; Pu, Qikang; Li, Yongxin; Wang, Xixi; Jiang, Yang; Yang, Danni; Yang, Yi; Yang, Jinling; Sun, Chengjun
Highlights: A novel approach for identification of microorganism based on similarity match of chromatographic fingerprints is proposed. The factors of cultivation, SPME and identification on the profile of MVOCs are investigated. The proposed method for identification of microorganism is validated by analysis of pure strain culture and simulated samples. Abstract: A novel approach for rapid identification of three foodborne pathogens including Staphylococcus aureus, Vibrio parahaemolyticus and Shigella sonnei in foods by solid phase microextraction (SPME) coupled with gas chromatography–mass spectrometry (GC–MS) was established. After cultivation 24, 18 and 20 h for Staphylococcus aureus, Vibrio parahaemolyticus and Shigella sonnei, respectively, the microbial volatile organic compounds (MVOCs) were extracted with a SPME device equipped with divinylbenzene/carboxen/polydimethylsiloxane (DVB/CAR/PDMS) coated fibers. The DB-1701P column was applied for separation of MVOCs. A total of 17, 13 and 14 volatile organic compounds were identified as characteristic MVOCs of Staphylococcus aureus, Vibrio parahaemolyticus and Shigella sonnei, respectively. Similarity of the MVOC chromatographic fingerprints for the bacteria were calculated and compared, and the results showed that the established method is stable, reproducible, accurate and has the potential to identify the three bacteria in food samples.